(untitled) (World Science, 2020)
Introduction. The respiratory system lesions in patients with systemic lupus erythematosus have not been properly addressed by both clinicians and scientists yet, since the progression of these lesions is often asymptomatic. Objective. To identify and determine the nature and prevalence of respiratory system lesions in patients with systemic lupus erythematosus; to distinguish syntropic comorbid lesions, to determine their prevalence and their relationship with the age of patients, disease duration, and the severity of respiratory failure. Materials and methods. 370 patients (331 women and 39 men) with SLE were enrolled. They underwent comprehensive examinations and were stratified by age, duration, and the activity of SLE. The obtained data were processed in Microsoft Excel by means of descriptive statistics, χ2 test, and z-test for comparisons of two proportions; the relationships were considered to be statistically significant when p < 0.05. Results. 67.57% of patients with SLE had respiratory system lesions. Pneumosclerosis, pulmonary hypertension, pneumonitis, and pulmonary fibrosis were found to be syntropic comorbid lesions, i.e. pathogenetically associated with SLE. The prevalence of syntropic comorbid respiratory system lesions in patients with systemic lupus erythematosus depends on the age of patients, duration of the disease, and the severity of respiratory failure. Pneumosclerosis is more prevalent in elderly patients and patients with the SLE duration of more than 6 years. It was the cause of respiratory failure in 43.02% of patients; the condition was of the first degree of severity. Pulmonary hypertension is more prevalent in elderly patients and patients with the SLE duration of less than one year. It led to respiratory failure in 16.13% of patients; the respiratory failure was predominantly mild. Pneumonitis is more prevalent in young patients and patients with SLE duration of more than 10 years. It led to respiratory failure in 52.00% of patients, while 64.10% out of them had degree I respiratory failure. Pulmonary fibrosis is more prevalent in elderly patients and patients with the SLE duration of 1-5 years. It led to respiratory failure in 62.50% of patients, while 80.00% out of them had the first degree of this condition).